Clinical disease characteristics according to karyotype in Turner syndrome - Chae Young Yeo; Chan Jong Kim; Young Jong Woo; Dae Yeol Lee; Min Sun Kim; Eun Young Kim; Jong Duck Kim (Korean Pediatric Society, 2010)
Purpose : Turner syndrome (TS) is a disorder in which various anomalies can be accompanied, especially cardiovascular, renal, thyroid and auditory problems. The aim of this study is to identify the incidence of these disorders in patients with TS according to karyotype. Methods : We reviewed medical records of 90 patients with TS diagnosed by chromosomal analysis in 4 hospitals from Jan 1998 to Dec 2007. We evaluated these cases by prepared protocol of 4 medical problems. Results : The distribution of karyotype was 45,X (47.8%), mosaic pattern (34.4%) and structural aberration group (17.8 %). Renal anomalies, cardiovascular anomalies, thyroid disorders and auditory problems are accompanied in 4.4%, 10.0 %, 11.1% and 5.6%, respectively. 45,X group had renal anomalies (7.0%), cardiovascular anomalies (18.6%), thyroid disorders (9.3%) and auditory problems (11.6%). Mosaic group had renal anomalies (3.2%), thyroid disorders (12.9%), no cardiovascular anomalies and auditory problems. Structural aberration group had cardiovascular anomalies (6.3%), thyroid disorders (12.5%) and no other 2 problems. Patients with 45,X group had a significant higher incidence of cardiovascular anomalies (P=0.025). Conclusion : Our results indicate that there are differences clinically according to karyotype of TS, especially in incidence of cardiovascular anomalies.